Semi-Public Restructuring: Good Faith and Business Continuity in Indonesian Go-Public Company Bankruptcies - Itok Dwi Kurniawan; Ismawati Septiningsih; Rahayu Subekti; Sahat Poltak Siallagan; Fines Fatimah (Faculty of Law, Universitas Lampung, 2025)
Indonesia’s insolvency framework is currently suboptimal in accomodating rapid creditor enforcement with preserving viable firms, particularly publicly listed companies where market signaling and minority interests are at stake. This article proposes the adoption of a semi-public restructuring regime that combines private negotiation (pre-packs) with structured judicial oversight similar to scheme procedures, including limited moratorium and cram-down powers. Using a normative juridical method supported by case analysis (including Garuda’s dual-track restructuring) and interviews with supervisory judges, the paper: (1) identifies legal and practical shortcomings of PKPU/Bankruptcy under Law No. 37/2004; (2) compares UK Part 26A, US Chapter 11, and regional moratorium models; and (3) formulates statutory reforms to operationalize semi-public restructuring in Indonesia. The proposal rests on three core pillars: a mandatory insolvency test, a time-bound moratorium to facilitate rescue, and judicially supervised cram-down with strengthened disclosure obligations to safeguard minority creditors.